Obstacles to the use of differentiated teaching strategies from the point of view of gifted students in middle and high school - Al Harthy, Hanouf Bahian Mohammed (Journal of Educational and Psychological Sciences, 2018)
This study aimed to identify the most important obstacles to the use of differentiated teaching strategies from the point of view of the gifted female students in the intermediate and secondary stages in Jeddah. The study also examined the effect of the variables of the study: gender، academic qualification and years of experience for the teacher. To collect the data، it was distributed to a random sample of the gifted students in the middle and secondary schools in Jeddah city (70) with 40% of the study population. The results of the study showed that the obstacles in the teaching methods of gifted students came in a medium and an average of (3.31) according to the Likert five scale. At the field level، the field of assessment methods was highest (3.49) followed by teaching methods with an average of 3.39. The results showed that there were statistically significant differences between the estimates of the sample of the study to the degree of obstacles to using differentiated teaching strategies from the point of view of teachers and teachers of gifted students in middle and high school in Jeddah due to the variables of Nes، educational qualification، and years of experience. In the light of the results، a number of recommendations and proposals were presented to activate the differential teaching and overcome its obstacles.